What Geohistory Can Teach Us About Fundamental Causes of Health Inequities (Health Equity, 2022)
The causes of cancer health inequities are complex, multilevel, and intersectional. The typical disciplines and data used to address these inequities focus on public health, health services, clinical, and fundamental science. Fundamental causes such as systemic racism are a source of much health inequity, but a broader scope of fundamental causes may be considered. Geohistorical events may intersect with other fundamental causes of health inequities. In this study, an example of relationships between ancient geological events, slavery, and subsequent effects of systematic racism are identified. These relationships support the hypothesis that health inequities have deep and complex origins. Geohistorical factors precede social, economic, and political influences on health inequities, and suggest that a full understanding of cancer health inequities and their elimination may be informed by geohistorical events. Thus, addressing inequities may involve disciplines not typically involved in health equity collaborations, including geography, history, economics, political science, and others.